Dynamic Effects and Structural Change under Environmental Regulation in a CGE Model with Endogenous Growth - Roger Ramer (ETH Zurich, CER-ETH - Center of Economic Research, 2011)
In this paper, we use a CGE model with endogenous growth to study the interplay between environmental regulation, innovation and sectoral growth. We find that a stringent reduction target for carbon emissions combined with a CO2-tax leads to structural changes. Under the assumption of a unilateral policy, the economy specializes in producing the energy-extensive good. Coupling the carbon tax with policies that aim at directly supporting sectoral capital accumulation significantly mitigates the negative impacts on competitiveness and growth. Finally, we identify two parameters that play an important role in applied energy policy analysis. First, the assumptions on the substitutability between fossil and non-fossil energy strongly affect the effectiveness of a given policy. When fossil and non-fossil energy are good substitutes, structural change in the economy is far less pronounced than under relative complementarity. Second, the rate of pure time preference has a pronounced impact on the investment incentives and thus on long-run development. Increasing the discount rate from 0.9% to 4.5% leads to a contraction in investments and to lower growth rates in all sectors.
Keywords: C68; O31; O41; Q43; 330; Energy and growth; CGE model; induced innovation; structural change; Umweltstandard; Innovation; Wirtschaftswachstum; CGE-Modell; Allgemeines Gleichgewicht; Endogenes Wachstumsmodell; Theorie